Membentuk Generasi Emas: Inovasi dan Transformasi Pendidikan SMAN 02 Kepahiang di Era Digital - Carles (JPT : Jurnal Pendidikan Tematik, 2025)
The digital era presents new challenges and opportunities in the world of education, especially in efforts to form a globally competitive golden generation. SMA 02 Kepahiang responds to this change through educational innovation and transformation that focuses on strengthening character, mastering technology, and improving the quality of learning. Various strategic programs are implemented, including the integration of technology in the learning process, developing a digital-based curriculum, and empowering students in digital literacy. This study aims to examine the effectiveness of these strategies in creating an adaptive and innovative learning environment. The results of the study show that educational transformation at SMA 02 Kepahiang is able to improve students' academic and non-academic competencies, while equipping them with 21st century skills. With this approach, it is hoped that SMA 02 Kepahiang can become a modern education model that is relevant amidst the challenges of the digital era.